Evaluation of the interface of green bilayer powder compact (BPC) of iron (Fe) under different die wall conditions - Mohd Yusoff, Syamimi; Mohd Tahir, Suraya; Mohamed Ariff, Azmah Hanim; Supeni, Eris Elliandy; Anuar, Mohd Shamsul (Universiti Putra Malaysia, 2023)
The current work evaluates cross-sectioned green bilayer powder compact (green BPC) of iron (Fe) under different die conditions. At first, finite element-based (FE) simultaneous compaction modelling is used to model the uniaxial, one-sided compaction of the green BPC of Fe and its interface. A Tri-mesh of 0.03 mm and mesh refinement along the interfacial boundary is set up with the condition of each node from both sides of layers (namely lower layer, L and upper layer, U) is mapped precisely to ensure its mutual interconnection along the horizontal edges of interface. Additionally, the modelling part utilised and validated our recently proposed image analysis under the metallographic technique’s standard framework. Our approach to model the interface to gain the same effect as from the experimental result of green BPC of Fe is in good agreement. It is significantly found that the use of the lubricated die condition contributed to increasing the local RD distribution along the interface of the green BPC of Fe. In contrast, the distribution is gradually dissuaded from the interface for the unlubricated die condition as the applied height: diameter (H:D) ratio increases.